Role of Proteomics in Crop Stress Tolerance - Ahmad, Parvaiz; Abdel Latef, Arafat A. H.; Rasool, Saiema; Akram, Nudrat A.; Ashraf, Muhammad; Gucel, Salih (Frontiers in Plant Science, 2016)
Plants often experience various biotic and abiotic stresses during their life cycle. The abiotic stresses include mainly drought, salt, temperature (low/high), flooding and nutritional deficiency/excess which hamper crop growth and yield to a great extent. In view of a projection 50% of the crop loss is attributable to abiotic stresses. However, abiotic stresses cause a myriad of changes in physiological, molecular and biochemical processes operating in plants. It is now widely reported that several proteins respond to these stresses at pre- and post-transcriptional and translational levels. By knowing the role of these stress inducible proteins, it would be easy to comprehensively expound the processes of stress tolerance in plants. The proteomics study offers a new approach to discover proteins and pathways associated with crop physiological and stress responses. Thus, studying the plants at proteomic levels could help understand the pathways involved in stress tolerance. Furthermore, improving the understanding of the identified key metabolic proteins involved in tolerance can be implemented into biotechnological applications, regarding recombinant/transgenic formation. Additionally, the investigation of identified metabolic processes ultimately supports the development of antistress strategies. In this review, we discussed the role of proteomics in crop stress tolerance. We also discussed different abiotic stresses and their effects on plants, particularly with reference to stress-induced expression of proteins, and how proteomics could act as vital biotechnological tools for improving stress tolerance in plants.